1984
DOI: 10.1038/clpt.1984.84
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous disopyramide: Safety and efficacy of a new dosage regimen

Abstract: The efficacy and safety of a new dosage regimen of intravenous disopyramide in ventricular arrhythmias were evaluated in 10 patients. Each had at least four premature ventricular contractions (PVCs)/min during a 30-min period before dosing. By the classification of Lown et al., grade III arrhythmia was present in four patients, grade IVA in three patients, and grade IVB in three patients. Disopyramide was injected intravenously as a bolus of 0.5 mg/kg over 5 min. Each patient received two to three additional b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A recent report (Reddy et al 1984) has shown that a satisfactory conversion of arrhythmias can be achieved giving the bolus injection in refract doses. Haemodynamic parameters, however, were not measured in this study.…”
mentioning
confidence: 99%
“…A recent report (Reddy et al 1984) has shown that a satisfactory conversion of arrhythmias can be achieved giving the bolus injection in refract doses. Haemodynamic parameters, however, were not measured in this study.…”
mentioning
confidence: 99%